O-036 Treatment of Intracranial Aneurysms with the LUNA AES: Midterm Clinical and Angiographic Follow-Up. (26th July 2014) - Piotin, M; Biondi, A; Sourour, N; Blanc, R
Abstract : Purpose: The LUNA is a self-expanding ovoid device that serves as an intra saccular flow diverter as well as a scaffold for endothelization across the neck. The objective of this prospective clinical study (9 European centers) aiming to include a total of 63 patients was to evaluate the ability of the AES to occlude intracranial aneurysms while maintaining patency of the parent artery. Methods: Immediate post-implantation occlusion grade, near-complete, or incomplete, and parent vessel compromise were evaluated. Patients underwent neurological testing with the NIHSS at baseline and time of discharge. Follow-up included clinical assessment at one, 3, 6, 9 and 12 months, and angiographic follow-up at 6 and 12 months. Results: In 5 cases, the LUNA AES placement was carried out with balloon microcatheter assistance. In 2 cases, the LUNA AES placement was carried out with a stent (Table 1 ). Clinical and angiographic immediate results and at follow up are summarised in Table 2 . Adverse events are summarised in Table 3 . Conclusion: Preliminary results demonstrate good safety profile. Angiographic follow up are promising. The clinical and angiographic follow-up will be extended to 36 months. Disclosures: M. Piotin: 2; C; Covidien, Stryker, Balt, MicroVention, Reverse Medical, Neuravi, Penumbra. A. Biondi: None. N. Sourour: 2; C; Covidien, Penumbra. R. Blanc: 2; C; Covidien, Stryker, Balt, MicroVention, Reverse Medical, Neuravi, Penumbra.